Method for producing silica dispersion for magnetic disks

By using a silica dispersion with specific particle size distributions and void diameters in the polishing liquid composition, the method addresses the challenges of improving polishing speed and reducing scratches and undulations on magnetic disk substrates, enhancing their surface quality and recording density.

JP7662350B2Active Publication Date: 2025-04-15KAO CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021022013
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-15
Publication Date
2025-04-15
Estimated Expiration
2041-02-15

AI Technical Summary

Technical Problem

Magnetic disk drives require improved surface quality with reduced scratches, undulations, and increased polishing speed, which existing technologies struggle to achieve effectively.

Method used

A silica dispersion is produced by mixing silica particles with different average primary particle diameters (25 nm to 70 nm, 10 nm to 24 nm, and 1 nm to 9 nm) and specific void diameters after drying, which is then used in a polishing liquid composition to enhance polishing efficiency and surface quality.

Benefits of technology

The method achieves increased polishing speed, reduced scratches, and minimized undulations on the substrate surface, thereby improving the recording density and surface quality of magnetic disk substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662350000001
    Figure 0007662350000001
Patent Text Reader

Abstract

To provide a polishing liquid composition that can achieve improved polishing rates, reduced scratches, and reduced undulations.SOLUTION: A method for producing a silica dispersion for magnetic disks includes mixing silica particles a with an average primary particle size of 25 nm or more and 70 nm or less, silica particles b with an average primary particle size of 10 nm or more and 24 nm or less, and silica particles c with an average primary particle size of 1 nm or more and 9 nm or less. After drying the silica dispersion at 300°C for 90 minutes, the voids have a diameter of 5 nm or more and less than 20 nm.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a method for producing a silica dispersion for magnetic disks, a silica dispersion for magnetic disks, a polishing liquid composition for magnetic disk substrates, a method for polishing a substrate, and a method for producing a magnetic disk substrate. [Background technology]

[0002] In recent years, magnetic disk drives have become smaller and have larger capacities, and higher recording densities are being demanded. To achieve higher recording densities, technological developments are being made to reduce the unit recording area and lower the flying height of the magnetic head in order to improve the detection sensitivity of weakened magnetic signals. In order to lower the flying height of the magnetic head and ensure a sufficient recording area, there are increasingly strict requirements for magnetic disk substrates in terms of improving smoothness and flatness, as typified by reducing surface roughness, waviness, and edge sagging (roll-off), and reducing defects, as typified by reducing scratches, protrusions, pits, etc.

[0003] In response to such demands, for example, Patent Document 1 discloses a polishing composition that contains non-spherical silica particles, spherical silica particles, and water, has a pH of 0.5 or more and 6.0 or less, and has an average minor axis of 105 nm or more that is larger than the average minor axis of the spherical silica particles. Patent Document 2 discloses a method of polishing a substrate using a polishing composition containing an abrasive having an average particle size of 1 to 30 nm and water, and having a filling rate of 79 to 90% by weight. Patent Document 3 discloses a polishing composition containing two or more types of abrasives, the polishing composition containing an abrasive having a zeta potential of more than 0 mV and an abrasive having a zeta potential of less than 0 mV at the pH during polishing. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2017 / 094592 [Patent Document 2] JP 2008-12668 A [Patent Document 3] JP 2006-306924 A Summary of the Invention [Problem to be solved by the invention]

[0005] With the increase in capacity of magnetic disk drives, the required characteristics for the surface quality of substrates are becoming more severe, and there is a demand for a polishing composition that can improve the polishing speed and reduce scratches and waviness on the substrate surface. In general, there is a trade-off between the polishing speed and scratches and waviness, and for example, there is a problem that if the polishing speed is improved, scratches and waviness on the substrate surface after polishing increase.

[0006] Therefore, the present disclosure provides a method for producing a silica dispersion for magnetic disks, which can achieve an improved polishing rate and reduced scratches and waviness, a silica dispersion for magnetic disks, a polishing liquid composition for magnetic disk substrates, and a method for polishing a substrate and a method for producing a magnetic disk substrate using the same. [Means for solving the problem]

[0007] In one aspect, the present disclosure relates to a method for producing a silica dispersion for magnetic disks, the method comprising mixing silica particles a having an average primary particle diameter of 25 nm or more and 70 nm or less, silica particles b having an average primary particle diameter of 10 nm or more and 24 nm or less, and silica particles c having an average primary particle diameter of 1 nm or more and 9 nm or less, wherein the silica dispersion has a void diameter of 5 nm or more and less than 20 nm after drying at 300° C. for 90 minutes.

[0008] In one aspect, the present disclosure relates to a silica dispersion for magnetic disks obtained by the production method of the present disclosure.

[0009] In one aspect, the present disclosure relates to a polishing liquid composition for magnetic disk substrates, which comprises a silica dispersion obtained by the production method of the present disclosure.

[0010] In one aspect, the present disclosure relates to a method for polishing a substrate, comprising polishing a substrate to be polished with the polishing liquid composition of the present disclosure, wherein the substrate to be polished is a substrate used in the manufacture of magnetic disk substrates.

[0011] In one aspect, the present disclosure relates to a method for producing a magnetic disk substrate, the method including a polishing step of polishing a substrate to be polished with the polishing liquid composition of the present disclosure. Effect of the Invention

[0012] According to one or more embodiments of the present disclosure, an effect can be achieved in that a silica dispersion capable of improving the polishing rate and reducing scratches and waviness can be produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present disclosure is based on the finding that by using a silica dispersion containing three types of silica particles differing in average primary particle size and having a predetermined void size for polishing a magnetic disk substrate, the polishing rate can be improved and scratches and waviness on the substrate surface after polishing can be reduced.

[0014] That is, in one aspect, the present disclosure relates to a method for producing a silica dispersion for magnetic disks (hereinafter, "the method for producing the present disclosure"), which includes mixing silica particles a having an average primary particle diameter of 25 nm or more and 70 nm or less, silica particles b having an average primary particle diameter of 10 nm or more and 24 nm or less, and silica particles c having an average primary particle diameter of 1 nm or more and 9 nm or less, and the silica dispersion has a void diameter of 5 nm or more and less than 20 nm after drying at 300° C. for 90 minutes. According to the method for producing the present disclosure, a silica dispersion can be provided that can improve the polishing rate and reduce scratches and waviness.

[0015] Although the details of the mechanism by which the effects of the present disclosure are manifested are not clear, it is presumed as follows. The general mechanism of polishing speed is thought to be due to the cutting depth of the particles relative to the substrate and the moving speed of the particles relative to the substrate. However, if the cutting depth of the substrate is increased by increasing the diameter of the particles, the polishing speed improves but there is a trade-off in that scratches increase. Furthermore, the moving speed of the particles is largely influenced by external factors such as the rotation speed of the polishing plate. Therefore, in this disclosure, we focus on the contact area of ​​the particles with the substrate. Normally, when particles of a single particle size are mixed together, the gaps between the particles are large, and the contact area of ​​the particles with the substrate does not increase, resulting in a low polishing rate. On the other hand, in this disclosure, by mixing three types of particles with different particle sizes, it is believed that small particles enter the gaps between the large particles, and the gaps between the particles become extremely small. It is estimated that the gaps between the particles become small and have a specific gap diameter, which improves the contact area with the substrate and improves the polishing rate. In addition, it is estimated that the improved contact area reduces the cutting depth of each of the large diameter particles mixed, reducing scratches and waviness. However, the present disclosure need not be construed as being limited to these mechanisms.

[0016] In the present disclosure, the "waviness" of a substrate refers to unevenness on the substrate surface having a longer wavelength than the roughness. In the present disclosure, for example, waviness observed at a wavelength of 60 to 160 μm is referred to as "short wavelength waviness", and for example, waviness observed at a wavelength of 500 to 5000 μm is referred to as "long wavelength waviness". By reducing the waviness (short wavelength waviness, long wavelength waviness) of the substrate surface after polishing, the flying height of the magnetic head in a magnetic disk drive can be reduced, and the recording density of the magnetic disk can be improved. The waviness (short wavelength waviness, long wavelength waviness) of the substrate surface can be measured, for example, by the method described in the Examples. In the present disclosure, "reduction of waviness" refers to reduction of at least one of the short wavelength waviness and the long wavelength waviness. In the present disclosure, scratches on the substrate surface can be detected, for example, by an optical defect inspection device and can be quantitatively evaluated as the number of scratches. The number of scratches can be specifically evaluated by the method described in the Examples.

[0017] [Mixing process] In the manufacturing method of the present disclosure, mixing silica particles a, silica particles b, and silica particles c (hereinafter also referred to as "mixing step") includes, in one or more embodiments, mixing silica particles a, silica particles b, silica particles c, water, and other components as necessary. Here, "mixing" includes mixing silica particles a, b, and c, water, and other components as necessary simultaneously or in any order. Silica particles a, b, and c may each be one type, or a combination of two or more types. Note that silica particles a, b, and c, water, and other components will be described later.

[0018] In one or more embodiments, the mixing step is preferably a step of mixing the silica dispersion so that the pore size becomes 5 nm or more and less than 20 nm after drying for 90 minutes at 300° C. Here, the drying conditions (300° C., 90 minutes) refer to drying conditions for completely removing the influence of water. Therefore, in one aspect, the present disclosure relates to a method for producing a silica dispersion for a magnetic disk, the method comprising mixing silica particles a, silica particles b, and silica particles c such that the silica dispersion has a void diameter of 5 nm or more and less than 20 nm after drying at 300° C. for 90 minutes.

[0019] The pore size after drying the silica dispersion at 300° C. for 90 minutes is 5 nm or more from the viewpoint of improving the polishing rate and reducing scratches and waviness, and from the same viewpoint, is less than 20 nm, preferably 18 nm or less, more preferably 15 nm or less, and even more preferably 12 nm or less. In the present disclosure, the pore size can be measured by the method described in the Examples.

[0020] In one or more embodiments, the mixing step is carried out so that the void volume of the silica dispersion after drying is less than or equal to 0.1 cm 3 / g or more 3.5cm 3 It is preferable that the silica particles a, the silica particles b, and the silica particles c are mixed together so that the silica particle size distribution becomes equal to or smaller than 1 / g. Thus, in one aspect, the present disclosure provides a method for preparing a silica dispersion having a void volume of 0.1 cm after drying. 3 / g or more 3.5cm 3 The present invention relates to a method for producing a silica dispersion for a magnetic disk substrate, the method comprising mixing silica particles a, silica particles b, and silica particles c so that the silica dispersion has a molecular weight of 1000 or less.

[0021] The void volume of the silica dispersion after drying is set to 0.1 cm from the viewpoint of improving the polishing rate and reducing scratches and waviness. 3 / g or more is preferable, and from the same viewpoint, 3.5 cm 3 / g or less is preferable, and 3 cm 3 / g or less is more preferable, and 2.5 cm 3 / g or less is more preferable, and 2 cm 3 In the present disclosure, the pore volume can be measured by the method described in the Examples.

[0022] In one or a plurality of embodiments, the mixing step is preferably a step of mixing the silica particles a, the silica particles b, and the silica particles c such that the water evaporation rate of the silica dispersion in an environment of 60° C. is 800 mg / h or less. Therefore, in one aspect, the present disclosure relates to a method for producing a silica dispersion for a magnetic disk substrate, the method comprising mixing silica particles a, silica particles b, and silica particles c so that the water evaporation rate of the silica dispersion in an environment of 60° C. is 800 mg / h or less.

[0023] The water evaporation rate of the silica dispersion in an environment of 60° C. is preferably 100 mg / h or more from the viewpoint of achieving reduction in scratches and waviness, and from the same viewpoint, is preferably 800 mg / h or less, more preferably 795 mg / h or less, even more preferably 790 mg / h or less, and even more preferably 785 mg / h or less. In the present disclosure, the water evaporation rate can be measured by the method described in the Examples.

[0024] In one or more embodiments, the mixing step is preferably a step of mixing silica particles a, silica particles b, and silica particles c such that the number ratio c' / (a'+b') satisfies the following formula (I), where a', b', and c' are the numbers of silica particles a, silica particles b, and silica particles c to be mixed, respectively. In the present disclosure, the number of each silica particle can be measured by the method described in the Examples. c' / (a'+b')≧2.5 (I) Here, in one or more embodiments, the value of the number ratio c' / (a'+b') may be calculated using the volume of one particle (particle volume) according to the following formula: The particle volume may be calculated from the average primary particle diameter of the silica particles. c' / (a'+b')=(content of silica particles c / particle volume of silica particles c) / {content of silica particles a / particle volume of silica particles a)+(content of silica particles b / particle volume of silica particles b)} Therefore, in one aspect, the present disclosure relates to a method for producing a silica dispersion for a magnetic disk substrate, the method comprising mixing silica particles a, silica particles b, and silica particles c such that the number ratio of the mixed silica particles a, silica particles b, and silica particles c satisfies the above formula (I).

[0025] From the viewpoint of reducing scratches and waviness, the number ratio c' / (a'+b') is preferably 2.5 or more, more preferably 5 or more, even more preferably 7.5 or more, and even more preferably 10 or more, and from the viewpoint of improving the polishing rate and reducing waviness, the number ratio c' / (a'+b') is preferably 50 or less, more preferably 40 or less, and even more preferably 30 or less. When the ratio of the numbers of silica particles a, silica particles b, and silica particles c to be mixed satisfies the above formula (I), the pore size, pore volume, and water evaporation rate tend to fall within the above-mentioned preferred ranges.

[0026] In one or more embodiments, the mixing step is preferably a step of mixing silica particles a, silica particles b, and silica particles c such that the content of silica particles a, silica particles b, and silica particles c in the silica dispersion is 10 mass% or more relative to the total content of silica particles a, silica particles b, and silica particles c. In the present disclosure, the content of silica particles is a value calculated as SiO2. In the present disclosure, the content of each component in the silica dispersion can be regarded as the blending amount of each component in the mixing step.

[0027] In the mixing step, the amount of silica particles a to be mixed is preferably 10% by mass or more, more preferably 14% by mass or more, and even more preferably 18% by mass or more, based on the total amount of silica particles a, b, and c, from the viewpoint of improving the polishing rate and reducing waviness, and is preferably 60% by mass or less, more preferably 50% by mass or less, and even more preferably 40% by mass or less, from the viewpoint of reducing scratches. When silica particles a are a combination of two or more kinds, the amount of silica particles a is the total amount thereof. In the mixing step, the amount of silica particles b to be mixed is preferably 10% by mass or more, more preferably 30% by mass or more, and even more preferably 50% by mass or more, based on the total amount of silica particles a, silica particles b, and silica particles c, from the viewpoint of improving the polishing rate and reducing waviness, and is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, from the viewpoint of reducing scratches. When silica particles b are a combination of two or more kinds, the amount of silica particles b is the total amount thereof. In the mixing step, the amount of silica particles c to be mixed is preferably 10% by mass or more, more preferably 12% by mass or more, and even more preferably 14% by mass or more, based on the total amount of silica particles a, silica particles b, and silica particles c, from the viewpoint of reducing scratches, and is preferably 30% by mass or less, more preferably 25% by mass or less, and even more preferably 20% by mass or less, from the viewpoint of improving the polishing rate and reducing waviness. When silica particles c are a combination of two or more kinds, the amount of silica particles c is the total amount thereof. By mixing the silica particles a, b, and c so that the number ratio thereof satisfies the above formula (I) and the contents of the silica particles a, silica particles b, and silica particles c in the silica dispersion are each 10 mass % or more relative to the total content of the silica particles a, b, and c, the pore size, the pore volume, and the water evaporation rate tend to fall within the above-mentioned preferred ranges.

[0028] [Silica particles a, b and c] In the mixing step, examples of the silica particles a, b, and c to be mixed include colloidal silica, fumed silica, pulverized silica, and silica obtained by surface-modifying these, with colloidal silica being preferred.

[0029] The average primary particle diameter of the silica particles a is, from the viewpoint of achieving an improvement in the polishing rate and a reduction in waviness, 25 nm or more, preferably 26 nm or more, and more preferably 27 nm or more, and from the viewpoint of reducing scratches, is 70 nm or less, preferably 50 nm or less, and more preferably 30 nm or less. The average primary particle diameter of the silica particles b is, from the viewpoint of achieving an improvement in the polishing rate and a reduction in waviness, 10 nm or more, preferably 14 nm or more, and more preferably 18 nm or more, and from the viewpoint of reducing scratches, is 24 nm or less, preferably 23 nm or less, and more preferably 22 nm or less. The average primary particle diameter of the silica particles c is, from the viewpoints of improving the polishing rate and reducing scratches and waviness, 1 nm or more, preferably 2 nm or more, and more preferably 3 nm or more, and from the same viewpoints, is 9 nm or less, preferably 8 nm or less, and more preferably 7 nm or less. In the present disclosure, the average primary particle size of the silica particles can be measured by the method described in the Examples.

[0030] In general, aqueous solutions of silica particles are alkaline. The pH of a 10 wt % aqueous solution of silica particles a or silica particles b is, for example, 9 or more and 10 or less. From the viewpoint of dispersibility, the pH of a 10 wt % aqueous solution of silica particles c is preferably 10.5 or more and 11.5 or less.

[0031] [Silica dispersion] In one aspect, the present disclosure relates to a silica dispersion for magnetic disks (hereinafter, also simply referred to as "silica dispersion of the present disclosure") obtained by the manufacturing method of the present disclosure. In one or more embodiments, the silica dispersion of the present disclosure contains silica particles a, silica particles b, silica particles c, and water. The pore size, pore volume, water evaporation rate, number ratio c' / (a'+b'), silica particle content, and content ratio of the silica dispersion of the present disclosure are preferably those described in the manufacturing method of the present disclosure above.

[0032] The total content of the silica particles a, b, and c in the silica dispersion of the present disclosure is preferably 15 mass% or more, more preferably 20 mass% or more, and even more preferably 25 mass% or more from the viewpoint of ease of production and transportation, and is preferably 60 mass% or less, more preferably 50 mass% or less, and even more preferably 40 mass% or less from the viewpoint of stability.

[0033] [water] Examples of the water contained in the silica dispersion of the present disclosure include distilled water, ion-exchanged water, pure water, and ultrapure water. The water content in the silica dispersion of the present disclosure is preferably 40 mass% or more, more preferably 50 mass% or more, and even more preferably 60 mass% or more from the viewpoint of stability, and is preferably 85 mass% or less, more preferably 80 mass% or less, and even more preferably 75 mass% or less from the viewpoint of ease of production and transportation.

[0034] [Other ingredients] In one or more embodiments, the silica dispersion of the present disclosure may further contain other components as necessary, within a range that does not impair the effects of the present disclosure. Examples of other components include preservatives, pH adjusters, etc.

[0035] The pH of the silica dispersion of the present disclosure is preferably 5 or more, more preferably 6 or more, and even more preferably 7 or more, from the viewpoint of improving the polishing rate and reducing scratches and waviness, and from the same viewpoint, it is preferably 11 or less, more preferably 10.5 or less, and even more preferably 10 or less. The pH of the silica dispersion of the present disclosure is preferably 5 to 11 or less, more preferably 6 to 10.5 or less, and even more preferably 7 to 10 or less, from the viewpoint of improving the polishing rate and reducing scratches and waviness. The pH can be adjusted using a known pH adjuster or the like. In the present disclosure, the above pH is the pH of the polishing composition at 25°C, and can be measured using a pH meter, and can be, for example, the value 2 minutes after immersing the electrode of the pH meter in the polishing composition.

[0036] [Polishing liquid composition] In general, the polishing composition can be obtained by mixing raw silica, water, and additives as necessary. In one or more embodiments, the silica dispersion of the present disclosure obtained by the manufacturing method of the present disclosure can be used as raw silica for the polishing composition used for polishing magnetic disk substrates. Therefore, in one aspect, the present disclosure relates to a method for producing a polishing liquid composition, comprising a step of blending the silica dispersion of the present disclosure, water, and, if necessary, additives, by a known method. Here, "blending" includes mixing the silica dispersion of the present disclosure, water, and, if necessary, additives, simultaneously or in any order, and the blending can be performed using a mixer such as a homomixer, a homogenizer, an ultrasonic disperser, or a wet ball mill. In one aspect, the present disclosure relates to a polishing liquid composition for magnetic disk substrates (hereinafter also referred to as the "polishing liquid composition of the present disclosure") that contains the silica dispersion obtained by the manufacturing method of the present disclosure. In one or more embodiments, the polishing liquid composition of the present disclosure may further contain water and, if necessary, an additive. In the present disclosure, the additive refers to a component other than raw material silica that can be blended into the polishing liquid composition used for polishing a magnetic disk substrate, and examples thereof include a water-soluble polymer, an acid, an oxidizing agent, a heterocyclic aromatic compound, an aliphatic amine compound, an alicyclic amine compound, a thickener, a dispersant, an anti-rust agent, a basic substance, an agent for improving the polishing rate, a surfactant, and the like.

[0037] The content of silica particles a in the polishing liquid composition of the present disclosure is preferably 0.6 mass % or more, more preferably 0.8 mass % or more, and even more preferably 1 mass % or more, from the viewpoint of improving the polishing rate and reducing waviness, and is preferably 4 mass % or less, more preferably 3.5 mass % or less, and even more preferably 3 mass % or less, from the viewpoint of reducing scratches. The content of silica particles b in the polishing liquid composition of the present disclosure is preferably 0.5 mass % or more, more preferably 1 mass % or more, and even more preferably 1.5 mass % or more, from the viewpoint of improving the polishing rate and reducing waviness, and is preferably 6 mass % or less, more preferably 5 mass % or less, and even more preferably 4 mass % or less, from the viewpoint of reducing scratches. The content of silica particles c in the polishing liquid composition of the present disclosure is preferably 0.6 mass % or more, more preferably 0.7 mass % or more, and even more preferably 0.8 mass % or more from the viewpoint of achieving reduced scratches and reduced waviness, and is preferably 2 mass % or less, more preferably 1.6 mass % or less, and even more preferably 1.2 mass % or less from the viewpoint of improving the polishing rate. The water content in the polishing liquid composition of the present disclosure is preferably 60 mass % or more, more preferably 70 mass % or more, and even more preferably 80 mass % or more from the viewpoint of usage costs, and is preferably 98 mass % or less, more preferably 97 mass % or less, and even more preferably 96 mass % or less, from the viewpoint of improving the polishing rate and reducing scratches and waviness. In the polishing liquid composition of the present disclosure, the ratio by number c' / (a'+b') of the silica particles a, b, and c is preferably as described in the production method of the present disclosure above.

[0038] In the present disclosure, the "content of each component in the polishing liquid composition" refers to the content of each component at the time of use, that is, at the time when the polishing liquid composition is started to be used for polishing. The polishing liquid composition of the present disclosure may be stored and supplied in a concentrated state within a range in which its storage stability is not impaired. In this case, it is preferable in that the manufacturing and transportation costs can be further reduced. The concentrate of the polishing liquid composition of the present disclosure may be appropriately diluted with the above-mentioned water as necessary when used. The dilution ratio is not particularly limited as long as the above-mentioned content of each component (at the time of use) can be secured after dilution, and may be, for example, 10 to 100 times.

[0039] The pH of the polishing liquid composition of the present disclosure is preferably 0.5 or more, more preferably 0.75 or more, and even more preferably 1 or more, from the viewpoint of achieving scratch reduction and waviness reduction, and is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less, from the viewpoint of achieving an improvement in the polishing rate and a reduction in scratches and waviness. The pH of the polishing liquid composition of the present disclosure is preferably 0.5 or more and 5 or less, more preferably 0.75 or more and 4 or less, and even more preferably 1 or more and 3 or less, from the viewpoint of achieving an improvement in the polishing rate and a reduction in scratches and waviness. The pH of the polishing liquid composition can be adjusted using a known pH adjuster or the like. In the present disclosure, the pH of the polishing liquid composition can be measured by the same method as that of the silica dispersion.

[0040] An embodiment of the polishing liquid composition of the present disclosure may be a so-called one-component type in which all components are premixed and supplied to the market, or a so-called two-component type in which components are mixed at the time of use.

[0041] [Polishing liquid kit] As described above, the silica dispersion of the present disclosure can be used as raw silica for a polishing liquid composition, and the raw silica can be filled into a container and used to produce a polishing liquid kit. Therefore, in one aspect, the present disclosure relates to a polishing liquid kit (hereinafter, "polishing liquid kit of the present disclosure") that contains the silica dispersion of the present disclosure obtained by the manufacturing method of the present disclosure filled in a container. The polishing liquid kit of the present disclosure can provide a polishing liquid composition that can improve the polishing rate and reduce scratches and waviness. The polishing liquid kit of the present disclosure may be, for example, a polishing liquid kit (two-liquid type polishing liquid composition) containing the silica dispersion liquid (first liquid) of the present disclosure and the additive aqueous solution (second liquid) containing the additive in a mutually unmixed state. The first liquid and the second liquid are mixed at the time of use, and diluted with water as necessary. The water contained in the first liquid may be the entire amount of water used to prepare the polishing liquid composition, or may be a part of the amount. The second liquid may contain a part of the water used to prepare the polishing liquid composition. The content of each component in the first liquid and the second liquid may be set so that the content of each component in the polishing liquid composition obtained by mixing them and further diluting them with water as necessary is the same as the content of each component in the polishing liquid composition of the present disclosure described above.

[0042] [Substrate to be polished] In one or more embodiments, the substrate to be polished is a substrate used for manufacturing a magnetic disk substrate. In one or more embodiments, the surface of the substrate to be polished is polished with the polishing composition of the present disclosure, and then a magnetic layer is formed on the substrate surface by sputtering or the like, thereby manufacturing a magnetic disk substrate.

[0043] The material of the substrate to be polished preferably used in the present disclosure includes, for example, metals or semimetals such as silicon, aluminum, nickel, tungsten, copper, tantalum, titanium, or alloys thereof, glassy materials such as glass, glassy carbon, amorphous carbon, ceramic materials such as alumina, silicon dioxide, silicon nitride, tantalum nitride, titanium carbide, and resins such as polyimide resin. Among them, the substrate to be polished is preferably a substrate to be polished that contains metals such as aluminum, nickel, tungsten, copper, or alloys mainly composed of these metals. As the substrate to be polished, for example, Ni-P plated aluminum alloy substrates, and glass substrates such as crystallized glass, reinforced glass, aluminosilicate glass, and aluminoborosilicate glass are more suitable, and Ni-P plated aluminum alloy substrates are even more suitable. In the present disclosure, the term "Ni-P plated aluminum alloy substrate" refers to an aluminum alloy substrate that has been subjected to electroless Ni-P plating after the surface of the aluminum alloy substrate is ground.

[0044] The shape of the substrate to be polished may be, for example, a shape having a flat surface such as a disk, plate, slab, or prism, or a shape having a curved surface such as a lens. Among them, a disk-shaped substrate to be polished is suitable. In the case of a disk-shaped substrate to be polished, the outer diameter is, for example, about 2 to 95 mm, and the thickness is, for example, about 0.4 to 2 mm.

[0045] In one or more embodiments, the polishing composition of the present disclosure can be suitably used for polishing a substrate after rough polishing. The substrate to be polished can be a substrate after rough polishing. Examples of abrasive grains used for rough polishing include alumina, silica, and the like.

[0046] [Substrate polishing method] In one aspect, the present disclosure relates to a method for polishing a substrate (hereinafter also referred to as the "polishing method of the present disclosure"), which comprises polishing a substrate to be polished using the polishing liquid composition of the present disclosure, and the substrate to be polished is a substrate used in the manufacture of a magnetic disk substrate. By using the polishing method of the present disclosure, it is possible to produce a high-quality magnetic disk substrate with reduced scratches and waviness on the substrate surface after polishing with high yield and good productivity. As described above, the substrate to be polished in the polishing method of the present disclosure includes those used in the manufacture of magnetic disk substrates, and among them, substrates used in the manufacture of magnetic disk substrates for perpendicular magnetic recording are preferred. The polishing method and conditions can be the same as those of the substrate manufacturing method of the present disclosure described below.

[0047] In one or more embodiments, polishing a substrate to be polished with the polishing liquid composition of the present disclosure means supplying the polishing liquid composition of the present disclosure to the surface to be polished of the substrate to be polished, bringing a polishing pad into contact with the surface to be polished, and moving at least one of the polishing pad and the substrate to be polished to perform polishing, or means sandwiching the substrate to be polished between a platen to which a polishing pad such as a nonwoven organic polymer-based abrasive cloth is attached, and polishing the substrate to be polished by moving the platen and the substrate to be polished while supplying the polishing liquid composition of the present disclosure to a polishing machine.

[0048] [Method of manufacturing magnetic disk substrate] In general, a magnetic disk is manufactured by polishing a substrate to be polished after a grinding process through a rough polishing process and a finish polishing process, and forming the substrate into a magnetic disk in a recording part forming process. The polishing composition of the present disclosure can be used in a polishing process, preferably a finish polishing process, for polishing a substrate to be polished in a method for manufacturing a magnetic disk substrate. That is, in one aspect, the present disclosure relates to a method for manufacturing a magnetic disk substrate (hereinafter also referred to as the substrate manufacturing method of the present disclosure) including a process for polishing a substrate to be polished using the polishing composition of the present disclosure (hereinafter also referred to as the "polishing process"). The substrate manufacturing method of the present disclosure is particularly suitable for a method for manufacturing a magnetic disk substrate for a perpendicular magnetic recording system.

[0049] In one or more embodiments, the polishing step in the substrate manufacturing method of the present disclosure is a step of supplying the polishing liquid composition of the present disclosure to the surface of the substrate to be polished, bringing a polishing pad into contact with the surface to be polished, and moving at least one of the polishing pad and the substrate to be polished to perform polishing. In one or more embodiments, the polishing step in the substrate manufacturing method of the present disclosure is a step of sandwiching the substrate to be polished between plates to which a polishing pad such as a nonwoven organic polymer-based polishing cloth is attached, and moving the platen and the substrate to be polished while supplying the polishing liquid composition of the present disclosure to a polishing machine to polish the substrate to be polished.

[0050] When the polishing process of the substrate to be polished is performed in multiple stages, the polishing process in the substrate manufacturing method of the present disclosure is preferably performed after the second stage, and more preferably performed in the final polishing process or the finish polishing process. In this case, in order to avoid the mixing of abrasive grains and polishing liquid composition from the previous process, separate polishing machines may be used for each step, and when separate polishing machines are used, it is preferable to wash the substrate to be polished after each polishing process. Furthermore, the polishing liquid composition of the present disclosure can be used in circulating polishing in which the used polishing liquid is reused. The polishing machine is not particularly limited, and a known polishing machine for substrate polishing can be used.

[0051] The polishing pad used in the present disclosure is not particularly limited, and for example, a suede type, a nonwoven fabric type, a polyurethane independent foam type, or a two-layer type in which these are laminated can be used. From the viewpoint of improving the polishing rate, a suede type polishing pad is preferred.

[0052] The polishing load in the polishing step of the substrate manufacturing method of the present disclosure is preferably 5.9 kPa or more, more preferably 6.9 kPa or more, and even more preferably 7.5 kPa or more from the viewpoint of improving the polishing rate, and is preferably 20 kPa or less, more preferably 18 kPa or less, and even more preferably 16 kPa or less from the viewpoint of reducing scratches. In the substrate manufacturing method of the present disclosure, the polishing load refers to the pressure of the platen applied to the polishing surface of the substrate to be polished during polishing. The polishing load can be adjusted by applying air pressure or a weight to at least one of the platen and the substrate to be polished.

[0053] In the polishing step of the substrate manufacturing method of the present disclosure, the supply rate of the polishing composition of the present disclosure is set to 1 / cm 2 of the substrate to be polished from the viewpoint of reducing scratches. 2 The flow rate is preferably 0.05 mL / min or more and 15 mL / min or less, more preferably 0.06 mL / min or more and 10 mL / min or less, even more preferably 0.07 mL / min or more and 1 mL / min or less, and even more preferably 0.07 mL / min or more and 0.5 mL / min or less.

[0054] The method of supplying the polishing liquid composition of the present disclosure to the polishing machine can be, for example, a method of continuously supplying the composition using a pump or the like. When supplying the polishing liquid composition to the polishing machine, in addition to a method of supplying the composition as a single liquid containing all components, the composition can be divided into a plurality of blending component liquids and supplied as two or more liquids, taking into consideration the stability of the polishing liquid composition, etc. In the latter case, the above-mentioned plurality of blending component liquids are mixed, for example, in the supply pipe or on the substrate to be polished, to form the polishing liquid composition of the present disclosure.

[0055] According to the substrate manufacturing method of the present disclosure, by using the polishing liquid composition of the present disclosure, it is possible to achieve the effect of producing high-quality magnetic disk substrates with reduced scratches on the substrate surface after polishing, with high yield and good productivity. EXAMPLES

[0056] The present disclosure will be described in more detail below with reference to examples, but these are merely illustrative and the present disclosure is not limited to these examples.

[0057] 1. Preparation of Silica Dispersion (Examples 1 to 5 and Comparative Examples 1 to 6) Silica dispersions (pH 10) of Examples 1 to 5 and Comparative Examples 1 to 6 were prepared by mixing silica particles a, silica particles b, and silica particles c shown in Table 1 with water to obtain the mass ratios shown in Table 1. The total content (effective content) of silica particles a, b, and c in each silica dispersion was 30 mass%, and the water content in each silica dispersion was 70 mass%. In preparing the silica dispersion, the following silica particles a, b and c were used. (Examples 1 to 5 and Comparative Examples 1 to 5) Silica particles a: Colloidal silica aqueous dispersion (Cataloid SI-50W, 40% by mass, pH 9.1), manufactured by JGC Catalysts and Chemicals Silica particles b: Colloidal silica aqueous dispersion (Cataloid SI-40W, 40% by mass, pH 9.1), manufactured by JGC Catalysts and Chemicals Silica particles c: Colloidal silica aqueous dispersion (Cataloid SI-550W, 20% by mass, pH 10.6), manufactured by JGC Catalysts and Chemicals Comparative Example 6 Silica particles a: colloidal silica aqueous dispersion (40% by mass, pH 9), manufactured by DuPont Silica particles b: colloidal silica aqueous dispersion (40% by mass, pH 9), manufactured by DuPont Silica particles c: Colloidal silica aqueous dispersion (20% by mass, pH 10), manufactured by Nissan Chemical Industries, Ltd.

[0058] 2. Preparation of Polishing Composition Polishing liquid compositions (pH 1.2) were prepared by mixing and stirring the silica dispersions of Examples 1 to 5 and Comparative Examples 1 to 6, sulfuric acid, hydrogen peroxide, and water. The content (effective amount) of each component in each polishing liquid composition was 6 mass% for silica particles, 0.7 mass% for sulfuric acid, and 0.02 mass% for hydrogen peroxide. The content of water is the remainder excluding the silica particles, sulfuric acid, and hydrogen peroxide. In preparing each polishing composition, the following sulfuric acid and hydrogen peroxide were used. Sulfuric acid: 62.5% refined dilute sulfuric acid manufactured by Teika Hydrogen peroxide: ADEKA 35% hydrogen peroxide

[0059] 3. Measurement of each parameter [Measurement of the average primary particle size of silica particles] Using a field emission scanning electron microscope (S-4800) manufactured by Hitachi High-Technologies Corporation, images were taken at random in 10 fields of view at a scanning voltage of 10 kV and a magnification of 200 K. As the object to be photographed, copper grit on which a carbon film was vapor-deposited was subjected to hydrophilization treatment, and several drops of an aqueous solution in which the aqueous dispersion of each silica particle was diluted to 0.1 mass % were dropped onto it. After that, the sample was dried overnight at room temperature to obtain a sample. The image data obtained by the above method was used to digitize the particle shapes and calculate the circle-equivalent diameter for a parameter of 1,000 or more particles using image analysis software (WinROOF2013) manufactured by Mitani Shoji Co., Ltd. Based on this value, the D50 value was determined as the average primary particle diameter.

[0060] [pH measurement] The pH of the polishing composition was measured at 25° C. using a pH meter (manufactured by DKK-Toa Corporation), and the value measured 2 minutes after immersing the electrode in the polishing composition was recorded.

[0061] [Quantity ratio] First, the volume of each silica particle (particle volume) is calculated using the formula: 3 / 4πr 3 (where π=3.14, r=average primary particle diameter / 2). Here, the average primary particle diameter is as shown in Table 1. As a result of the calculation, in Examples 1 to 5 and Comparative Examples 1 to 5, the particle volume (nm 3 , the same below) was 6462, the particle volume of silica particles b was 2355, and the particle volume of silica particles c was 37. In Comparative Example 6, the particle volume of silica particles a was 2726, the particle volume of silica particles b was 808, and the particle volume of silica particles c was 150. The ratio of the number of silica particles a, b, and c to be mixed was calculated from the following formula. The results are shown in Table 1. (Examples 1 to 5 and Comparative Examples 1 to 5) Number ratio c' / (a'+b')=(content of silica particles c / 37) / {(content of silica particles a / 6462)+(content of silica particles b / 2355)} Comparative Example 6 Number ratio c' / (a'+b')=(content of silica particles c / 150) / {(content of silica particles a / 2726)+(content of silica particles b / 808)}

[0062] [Measurement of pore diameter and total pore volume] The silica dispersion was left to stand in a dryer at 110°C for three days to evaporate most of the water. The resulting silica powder was then crushed in an agate mortar. The crushed silica powder was pre-baked at 300°C for 90 minutes in a pore analyzer (ASAP-2020) to completely evaporate the water, after which the pore distribution was calculated using physical adsorption with nitrogen gas. The following equation holds during the adsorption isothermal process. Ln(p / p0)=-2VLγcosθ / rRT VL is the molar volume of a gas molecule liquefied by capillary condensation, γ is the surface tension, θ is the contact angle, and r is the radius of the pore. Based on the above formula, the pore volume and pore radius r at a certain relative pressure p / p0 are analyzed from the amount of gas adsorbed. The pore diameter indicates the value when the maximum pore volume is given, and the total pore volume is calculated from the value obtained by integrating the spectrum.

[0063] [Measurement of water evaporation rate in a 60℃ environment] The temperature of a general dryer was set to 60°C, and a certain amount of each type of silica dispersion adjusted to 10% by mass was placed in a glass tube and placed in the dryer. The mass loss after drying for 10 hours was then calculated and standardized in mg / h. This operation was also repeated three times, and the average value was calculated as the water evaporation rate.

[0064] 4.Polishing method The polishing compositions prepared using the silica dispersions of Examples 1 to 5 and Comparative Examples 1 to 6 were used to polish the following substrates under the following polishing conditions. The polishing rate, waviness, and number of scratches were then measured by the methods described below, and the results are shown in Table 1.

[0065] [Substrate to be polished] The substrate to be polished was a Ni-P plated aluminum alloy substrate that had been roughly polished with a polishing composition containing silica abrasive grains. The substrate had a thickness of 0.8 mm, an outer diameter of 95 mm, an inner diameter of 25 mm, and a center line average roughness Ra of 1 nm measured by an AFM (Digital Instrument NanoScope IIIa Multi Mode AFM).

[0066] [Polishing conditions] Polishing test machine: Double-sided polishing machine (manufactured by SpeedFam) Polishing pad: Fujibo CF4303 (suede type, foam layer: polyurethane elastomer, thickness 0.69 mm) Carrier: Aramid thickness 0.7nm (made by Sagami PCI) Polishing liquid composition supply amount: 100mL / min Lower surface plate rotation speed: 31.4rpm Polishing load: 140g / cm 2 Polishing time: 290 seconds Number of boards: 10 After polishing, the substrate is removed from the double-sided polisher and the surface is cleaned using an automatic cleaner.

[0067] 5. Evaluation [Evaluation of polishing speed] The weight of each substrate was measured before and after polishing using a tool (manufactured by Sartorius, "BP-210S"), and the mass loss was calculated from the change in mass of each substrate. The polishing rate was calculated by dividing the average mass loss of all 10 substrates by the polishing time using the following formula. The polishing rate measurement results for Examples 1 to 5 and Comparative Examples 1 to 6 are shown in Table 1 as relative values, with Comparative Example 1 taken as 100. Mass loss (g) = {mass before polishing (g) - mass after polishing (g)} Polishing speed (mg / min) = Mass reduction amount (mg) / Polishing time (min)

[0068] [Evaluation of short and long wavelength waviness] Two substrates were randomly selected from the 10 substrates after polishing, and measurements were made on both sides of each selected substrate at random four points (total of 16 points) under the following conditions. The average values ​​of the measurements at the 16 points were calculated as the short wavelength waviness and long wavelength waviness of the substrate. Then, relative values ​​were calculated with Comparative Example 1 set to 100, and the results are shown in Table 1. <Measurement conditions> Measuring device: New View 7300 (Zygo) Lens: 2.5x Zoom: 0.5x Short wavelength range: 60~160μm Long wavelength range: 50~500μm Analysis software: Zygo Metro Pro (Zygo)

[0069] [Scratch rating] Measuring instrument: Candela OSA7100, 6110 (KLA Tencor) Measurement recipe: 95T Substrate rotation speed: 10000 rpm Measurement mode: PSc, PScR Laser voltage: Circumferential laser voltage 650mV, radial laser voltage 600mV Evaluation: Four of the substrates were randomly selected from those placed in the polishing tester, and each substrate was irradiated with a laser at 10,000 rpm to measure the number of scratches. The total number of scratches on both sides of each of the four substrates was divided by 8 to calculate the number of scratches per substrate surface. The measurement results of the number of scratches in Examples 1 to 5 and Comparative Examples 1 to 6 are shown in Table 1 as relative values ​​with Comparative Example 1 being set at 100.

[0070] [Table 1]

[0071] As shown in Table 1 above, the silica dispersions of Examples 1 to 5 had improved polishing rates and reduced short-wavelength waviness, long-wavelength waviness, and scratches, compared to the silica dispersions of Comparative Examples 1 to 6. [Industrial Applicability]

[0072] According to the present disclosure, for example, it is possible to provide a magnetic disk substrate suitable for achieving high recording density.

Claims

1. A method for producing a silica dispersion, comprising mixing silica particles a having an average primary particle diameter of 25 nm or more and 70 nm or less, silica particles b having an average primary particle diameter of 10 nm or more and 24 nm or less, and silica particles c having an average primary particle diameter of 1 nm or more and 9 nm or less, The method for producing a silica dispersion for a magnetic disk, wherein the silica dispersion has a void diameter of 5 nm or more and less than 20 nm after drying at 300° C. for 90 minutes.

2. 2. The method for producing a silica dispersion for magnetic disks according to claim 1, wherein the number ratio c' / (a'+b') satisfies the following formula (I), where the numbers of silica particles a, silica particles b and silica particles c to be mixed are a', b' and c', respectively. c' / (a'+b')≧2.5 (I)

3. 3. The method for producing a silica dispersion for magnetic disks according to claim 1, wherein the content of each of the silica particles a, silica particles b, and silica particles c in the silica dispersion is 10 mass% or more relative to the total content of the silica particles a, silica particles b, and silica particles c.

4. The void volume after drying of the silica dispersion is 0.1 cm 3 / g or more 3.5cm 3 4. The method for producing a silica dispersion for magnetic disks according to claim 1, wherein the water evaporation rate in an environment of 60° C. is 800 mg / h or less and the water evaporation rate in an environment of 60° C. is 800 mg / h or less.

Citation Information

Patent Citations

  • Abrasive composition

    JP2002030274A

  • Polishing fluid composition

    JP2006306924A

  • Polishing-fluid composition

    JP2008012668A

  • Polishing liquid composition for hard and brittle material

    JP2015093931A

  • Polishing slurry for oxide single crystal substrate and method for producing the same

    JP2017043731A